Analysis in circular economy research in Latin America: A bibliometric review (2023)
Circular Economy (CE) plays a crucial role in Latin America, where the transition to new economic development models poses significant challenges. This study conducts a bibliometric analysis of CE research in the region to identify critical areas of development, influential authors, organizations, and future research trends. This analysis aims to highlight the progress made in the CE field in Latin America and identify areas for improvement to promote sustainable development. Using the Scopus database, we analyzed 632 research papers, and the rising number of CE publications in Latin America suggests a continuous growth trajectory, expected to reach over 2500 studies by 2026. The analysis reveals that Brazil leads CE research with 274 publications, Waste Management being the most studied topic. The study highlights the region's growing trend towards implementing innovative and sustainable solutions for waste management and resource utilization, such as bioengineering and biochemistry processes, which could positively impact the region's economy and environment. The findings of this study provide valuable insights for policymakers and researchers aiming to promote sustainable development in Latin America.